Pengaruh Terpaan Promosi Penjualan, Citra Merek dan Nilai Pelanggan terhadap Loyalitas Konsumen Aplikasi OVO di Semarang - Ichsan Wahyu Pratama; Tandiyo Pradekso (Interaksi Online, 2020)
This study aims to determine the effect of each variable, sales promotion exposure (X1), brand image (X2) and customer value (X3) on consumer loyalty in the OVO application (Y). In this study using quantitative research methods. The sampling technique used non-probability sampling with a total sample of 50 respondents using the OVO application in Semarang. The analysis used to test the hypothesis is a simple linear regression test. Hypothesis testing shows sales promotion exposure to consumer loyalty is 0.000 (<0.05), so there is an effect of sales exposure on consumer loyalty. The result of the significant value of brand image on consumer loyalty is 0.001 (<0.05), so there is an effect of brand image on consumer loyalty. While the significant value of customer value on customer loyalty is 0.037 (<0.05), so there is an effect of customer value on customer loyalty.